2007
DOI: 10.3171/jns.2007.106.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of experimental subarachnoid hemorrhage–induced cerebral vasospasm by the adenosine A2A receptor agonist CGS 21680

Abstract: This is the first evidence that adenosine A2A receptor agonism is effective in preventing SAH-induced vasospasm without significant complications. The beneficial effect of adenosine A2A receptor agonists may be, at least in part, related to the prevention of augmented expression of iNOS and the preservation of normal eNOS expression following SAH. Adenosine A2A receptor agonism holds promise in the treatment of cerebral vasospasm following SAH and merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Park et al also observed a reduction in eNOS protein in rats with SAH [26]. Recently, the eNOS-based therapeutics held the therapeutic promise in the treatment of cerebral vasospasm following SAH [21,27,28]. Our results revealed that AG treatment via the inhibition of iNOS activity significant reversed the decreased levels of eNOS mRNA and protein, and consequently ameliorating the cerebral vasospasm after the induction of SAH.…”
Section: Discussionsupporting
confidence: 58%
“…Park et al also observed a reduction in eNOS protein in rats with SAH [26]. Recently, the eNOS-based therapeutics held the therapeutic promise in the treatment of cerebral vasospasm following SAH [21,27,28]. Our results revealed that AG treatment via the inhibition of iNOS activity significant reversed the decreased levels of eNOS mRNA and protein, and consequently ameliorating the cerebral vasospasm after the induction of SAH.…”
Section: Discussionsupporting
confidence: 58%
“…A 2A AR mediated NO release is also well recognized in various endothelial cell culture studies, including human, rat and porcine [4,34,35]. In another study [36], the authors stated that L-NAME abrogates 1 nM CGS-21680 dilatory response in Langendorff mouse heart.…”
Section: Discussionmentioning
confidence: 87%
“…The role of JNK MAPK may well be crucial to cell survival and regeneration in SCI and may represent a target for pharmacological tools aimed at improving neuron recovery. Lin et al (12) demonstrated that the A 2A agonist ATL 202 rapidly and persistently reduces locomotor dysfunction and SC demyelination after SCI. Therefore, a reducing effect of JNK in oligodendrocytes might contribute to the protective effect of the A 2A selective agonist CGS 21680 against SCI-induced demyelination.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies report that selective activation of A 2A receptors inhibits proinflammatory responses in bone marrowYderived cells, including platelets, monocytes, some mast cells, neutrophils, and T cells (10,11). The work of Lin et al (12) in chimeric mice selectively lacking bone marrow A 2A receptors demonstrates that inflammatory bone marrowYderived cells are the primary targets of A 2A agonistYmediated protection from SCI. In in vivo models of SCI, A 2A agonism proved protective against different inflammatory readouts (6,13,14).…”
Section: Introductionmentioning
confidence: 97%